Cold formed steel and buckling criteria of cold formed steel purlins - Muftah, Fadhluhartini; Mohd Sani, Mohd Syahrul Hisyam (2009)
Cold formed steel member made up at room temperatures which cause the material may become harder and stronger. Generally there are two method of producing cold formed steel either by press breaking or cold forming depending on type and capacity of section required. Cold formed steel can be used either in general application or building application due to several advantages such as high strength, lightweight and cost-effective way of covering a wide variety of building structures. Cold forms steel purlin has are inherently sensitive to local, distorsional, and lateral-torsional buckling. This problem leads due to the thinner of the thickness of purlin in which cause the section undergoes both bending and twists from the beginning of loading. 7 m C35030 simply supported cold formed steel purlin subjected to uplift uniformly distributed load results that the purlin was experiencing lateral and torsion failure which the cross section rotates and translates, however it did not distorted in shape at the early stage of loading. Immediately before reaching the peak load at 11.53 kN/m, the section is experiencing a lateral torsional buckling where the web of the purlin buckles at the web-bottom flange junction.